ANALYSIS OF SIPPADU SUCCESS IN PUBLIC SERVICES AT DPMPTSP SIDOARJO - Fatih, M. Faishol; Choiriyah, Ilmi Usrotin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the determining factors influencing the success of the Integrated Licensing Service Information System (SIPPADU) in Sidoarjo Regency as a digital-based public service innovation. Method: A descriptive qualitative approach was employed by analyzing official documents from the One-Stop Investment and Integrated Services Office (DPMPTSP) and conducting in-depth interviews with SIPPADU officers. The data were then interpreted to identify both internal and external factors contributing to program effectiveness. Results: The findings indicate that the success of the SIPPADU program is shaped by a synergy between technical and non-technical elements. Internally, the competence of officials, continuous training, robust technological infrastructure, and simplified service procedures form the foundation of efficiency. Externally, strong regulatory support, intensive social media dissemination, and proactive outreach initiatives enhance public engagement. Despite these achievements, challenges persist in the form of low digital literacy among older citizens and traditional MSME actors, which limits inclusivity. Novelty: This study provides a contextual framework for understanding how the integration of technological innovation, human resource development, and communication strategies can strengthen digital governance and promote broader public participation in e-government services.